HLA-C*18:01 and KIR2DL2+C1 genetic variants are associated with low viral load in cART naïve HIV-infected adult Zimbabweans - Mhandire, Kudakwashe; Tshabalala, Mqondisi; Zijenah, Lynn Sodai; Mlambo, Tommy; Mhandire, Doreen Zvipo; Musarurwa, Cuthbert; Duri, Kerina; Matarira, Hilda Tendisa; Dandara, Collet; Rowland-Jones, Sarah L; Stray-Pedersen, Babill (The Journal of Infection in Developing Countries, 2018)
Introduction: Polymorphisms in killer cell immunoglobulin-like receptor (KIR) and human leukocyte antigen (HLA) gene families are implicated in differential outcomes of HIV infection. However, research findings on the influence of KIR and HLA-C polymorphism on HIV disease progression remain inconclusive. We thus investigated the association of KIR and HLA-C gene polymorphisms with plasma HIV load (VL) and CD4+ T lymphocyte (CD4) count in 183 chronically HIV-infected, combination antiretroviral therapy (cART) naïve Zimbabweans of Bantu origin. Methodology: The presence or absence of 15 KIR genes were determined using sequence specific primer polymerase chain reaction while HLA-C typing was performed using chain termination DNA sequencing. Plasma VL was determined using the Cavidi Exavir viral load version 3 assay while CD4+ T lymphocytes were enumerated using flow cytometry. VLs and CD4 counts were compared between gene/genotype carriers and non-carriers using Mann-Whitney ranksum test. Results: HLA-C*18:01 allele carriers had a significantly lower median log10 VL (2.87copies/mL [IQR;2.3-3.2]) than the non-C*18:01 carriers (3.33copies/mL [IQR; 2.74-3.9]), p = 0.018. Further, median log10 VL was significantly lower in KIR2DL2+C1 carriers (2.745 [IQR; 2.590-2.745]) than non-KIR2DL2+C1 carriers (3.4 [IQR; 2.746-3.412]), p = 0.041. Comparison of CD4 + T lymphocyte counts between C*08:02 allele carriers and non-C*08:02 carriers showed a significantly higher median CD4 count in C*08:02 carriers (548cells/µL [IQR;410-684]) than in non-carriers (428cells/µL [IQR;388-537]), p = 0.034. Conclusion: We conclude that the HLA-C*18:01 and KIR2DL2+C1 genetic variants are associated with low VL while the C*08:02 is associated with high CD4+ T lymphocyte count among cART naïve Zimbabwean adults with chronic HIV infection.